The Effect of English Listening Habit Towards Vocabulary Mastery - Ririn Rindiyanti; Winda Widyaningrum (JEdu: Journal of English Education, 2022)
Listening is something that everyone can do it, especially now that there are many media that use English as a basis for learning an aspect. The habit of listening to music, or sounds from films that use English makes the addition of vocabulary increases with time as a result of these habits. Regardless of what genres are listened to and what kind of films are served, if we often listen to something that is used in English, it will increase our understanding of the vocabulary we have. With many songs or films that use English, it will make our ears respond to the brain for what it receives. Because when we often listen to something using English the brain will respond quickly to whatever it gets. This makes the brain store more vocabulary that it receives. Therefore, from a habit will lead to a lot of understanding of what it gives to the brain.